Early hemostatic derangements in patients with de novo acute leukemia: A single center experience - Laith Alnuaimy, Sarah; P. Shamoon, Rawand (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Bleeding and thrombosis are major causes of morbidity and mortality in patients with acute leukemia (AL); they are attributed to hemostatic derangement and coagulation defects that are associated with leukemia. There is a paucity of information regarding coagulopathy in AL patients in our locality; this study, therefore, was employed to evaluate hemostatic parameters in patients with AL at the time of presentation. Methods: This prospective cross-sectional study included 84 newly diagnosed patients with AL. The study was carried out at Nanakali hemato-oncology center from September 2021 to May 2022. Patients were assessed for coagulation parameters including prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen level (FBG), D-dimer (D-Di), antithrombin (AT), protein C (PC), and protein S (PS). Results: The median age of the studied patients was 26 years with a male to female ratio of 1.1:1. Acute myeloid leukemia (AML) patients constitutes 51.2% (43 patients), and the remaining 41 (48.8%) patients had acute lymphoblastic leukemia (ALL). PT was significantly prolonged, D-Di was significantly higher and AT, and PC were significantly decreased in AML compared to control groups. Only D-Di level was significantly higher in ALL compared to control groups. Bleeding manifestations were encountered in 40 (47.6%) patients with a higher incidence among the AML group (28 patients, 70%). Thrombosis occurred in 2 (2.4%) patients. Conclusion: Defects of coagulation were common in AL. Hemostatic derangement and bleeding at the time of presentation were more noticeable in patients with AML.